DESIGN BROADBAND REFLECTARRAY USING E-SHAPED SLOT CIRCULAR MICROSTRIP ANTENNA: Communication (Diyala Journal of Engineering Sciences, 2015)
In this work, a circular E-shaped slot microstrip patch element is investigated to design a reflectarray. The E-shaped slot dimensions are varied to study, reflection properties of the patch antenna. It is discovered that the reflection properties and phase range of the proposed element can be optimized using the E-shaped slot's dimensions. The element's resonance and full parametric analysis were checked using a modern microwave software tool was involved to simulate. A 340o phase range is achieved easily;it is enough to design a small-size reflectarrays.